Pharmacogenetics of Anesthesia: An Integrative Review. Issue 4 (July 2016) - Aroke, Edwin N.; Dungan, Jennifer R.
Abstract : Background: Monitoring a patient's response to drug therapy and early identification of an adverse reaction are important responsibilities of nurses. Despite the relative safety of anesthesia practice, 1 in 20 perioperative medication administrations includes a medication error and/or adverse drug reaction. Although several factors contribute to an individual's response to medications, genetic predisposition accounts for over 50% of that response. Objective: The purpose of this review is to explore the evidence of genetic variability associated with response to volatile and intravenous anesthetics. Methods: A comprehensive search of published literature in PubMed, CINAHL, and Cochrane databases from 1960 to May 30, 2015, was performed. Iterative reading of the primary articles was performed to ensure congruence between the extracted data and the primary article and reduce the data to draw conclusions. Results: The analysis revealed that most anesthetics are metabolized by enzymes in the CYP2 and UGT1 family. CYP2B6 catalyzes propofol and ketamine metabolism. CYP2B6*6 allele is associated with decreased propofol and ketamine metabolism and increased adverse effects. Genetic variants in the UGT1A9 enzyme are associated with the need for higher induction dose and increased clearance of propofol. Discussion: Despite the significant gaps in the literature, current evidence suggests that close monitoring is required when administering anesthetics to individuals with the CYP2B6*6 allele. Future research to address identified gaps in this review may have the potential to identify underlying genetic contribution to anesthetic response and prevent significant adverse events during anesthesia delivery and perioperative nursing care.